The Effect of POSSE Strategy on Students’ Reading Comprehension Viewed by Their Reading Interest - Saras Puspita Anggraini; Annisa Astrid; Husnaini Husnaini (The Art of Teaching English as a Foreign Language (TATEFL), 2026)
Reading strategies are widely used to assist students in enhancing their reading comprehension. Additionally, reading interest is a critical factor in motivating students to use reading strategies effectively. However, many students still struggle to apply reading strategies, and research analyzing the impact of reading interest on the implementation of POSSE strategies is lacking. Therefore, the objective of this study is to examine the utilization of POSSE strategies to improve students’ reading comprehension, the impact of their reading interest levels on the reading comprehension scores, and the impact of students’ reading interest levels on the implementation of POSSE strategies to enhance reading comprehension. This quantitative experimental method employed a factorial design. The population consisted of eighth-grade students at SMPN 02 Belitang Mulya, and samples were selected using purposive sampling. Data were obtained from a reading comprehension test and a reading interest questionnaire, both tested for validity and reliability. The data were analyzed using two-way ANOVA. The findings reveal that: (1) the POSSE strategy significantly improved students’ reading comprehension; (2) students with high reading interest outperformed those with low interest; and (3) there was a significant difference between teaching strategy and reading interest. The findings showed that effective reading instruction involves integrating the POSSE strategy and cultivating reading interest, alongside differentiated support tailored to students' motivational levels, to enhance comprehension outcomes.